Offshore Wind Farms in the UK: Challenges and Risks in the development Process - Zhang, Yiping/Y (2009)
This paper is an output of a joint placement project with one energy company, seeking development in Offshore Wind market in the UK. The UK Government is giving strong policy backing to the expansion of the offshore wind sector. With the announcement of future Round 3, offshore wind energy market is receiving increasing attentions today. Yet this is a young industry and so little is known and understood about the market and the issues such as technology behind it. To help developers understand current offshore wind market in the UK, this paper examined the challenges and risks in the development process of offshore wind farms through the analysis of different players in OWF market. It found that major risks were associated with strong supplier power. It also summarised the findings from both of market‟s perception and the Company‟s perception. Gap analysis in terms of the differences in perception was conducted and implications for developers were concluded.